Poetry Writing Learning Contextual Learning Through Application Model (Contektual Teaching And Learning) Share Class Ix Student Smp Negeri 1 Painan South Coastal District - Imlafihasna Imlafihasna (Fakultas Sastra Universitas Ekasakti, 2017)
In the literary learning activities will be realized concretely through the reading and understanding of poetry, novels, short stories, romances, and drama text. The activities of understanding a literary work should be done in earnest so as to train and develop the sensitivity of the mind. While learning Indonesian language directed to improve the ability of students in communicating both orally and in writing and can foster an appreciation of a work of Indonesian literature. Learning poetry writing will also be able to develop the ability of students of class IX SMP Negeri 1 Painan using Contextual Model (contektual teanching and learning). With the development of contextual model (contexual teanching and learning), it is expected that the students will be more active and creative in learning Indonesian language especially in writing poetry lesson, and improving the quality of students' learning in terms of finding, finding and solving problems in learning. By actively and creatively breeding in searching for sources and in discussions as problem-solving efforts, students will really understand the learning materials. By mastering the learning materials, it allows them to get the optimal value and in turn the index of his presentation will increase. The change is one of them by using contextual model (contektual teanching and learning) as an effort to improve the ability to write poetry. Contextual modeling (contextual teanching and learning) is a system that stimulates the brain to construct patterns that embody meaning or a learning system that matches the brain that produces meaning by linking the academic content to the context of the student's daily life. In order to optimize the learning of the Indonesian language especially for the subject of writing poetry, it is necessary to conduct a classroom action research on